Cloning, overexpression, purification, and modeling of a lectin (Rhinocelectin) with antiproliferative activity from Tiger Milk Mushroom, Lignosus rhinocerus. Issue 10 (13th June 2019) - Cheong, P.C.H.; Yong, Y.S.; Fatima, A.; Ng, S.T.; Tan, C.S.; Kong, B.H.; Tan, N.H.; Rajarajeswaran, J.; Fung, S.Y.
Abstract: A lectin gene from the Tiger Milk Mushroom Lignosus rhinocerus TM02® was successfully cloned and expressed via vector pET28a in Escherichia coli BL21(DE3). The recombinant lectin, Rhinocelectin, with a predicted molecular mass of 22.8 kDa, was overexpressed in water‐soluble form without signal peptide and purified via native affinity chromatography Ni‐NTA agarose. Blast protein analysis indicated the lectin to be homologous to jacalin‐related plant lectin. In its native form, Rhinocelectin exists as a homo‐tetramer predicted with four chains of identical proteins consisting of 11 beta‐sheet structures with only one alpha‐helix structure. The antiproliferative activity of the Rhinocelectin against human cancer cell lines was concentration dependent and selective. The IC50 values against triple negative breast cancer cell lines MDA‐MB‐231 and breast cancer MCF‐7 are 36.52 ± 13.55 μg mL −1 and 53.11 ± 22.30 μg mL −1, respectively. Rhinocelectin is only mildly cytotoxic against the corresponding human nontumorigenic breast cell line 184B5 with IC50 value at 142.19 ± 36.34 μg mL −1 . The IC50 against human lung cancer cell line A549 cells is 46.14 ± 7.42 μg mL −1 while against nontumorigenic lung cell line NL20 is 41.33 ± 7.43 μg mL −1 . The standard anticancer drug, Doxorubicin exhibited IC50 values mostly below 1 μg mL −1 for the cell lines tested. Flow cytometry analysis showed the treated breast cancer cells were arrested at G0/G1 phase and apoptosis induced. Rhinocelectin agglutinated rat and rabbit erythrocytes at a minimal concentration of 3.125 μg mL −1 and 6.250 μg mL −1, respectively.